2016
DOI: 10.18632/oncotarget.10601
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal organization of white matter networks in patients with subjective cognitive decline and mild cognitive impairment

Abstract: Network analysis has been widely used in studying Alzheimer's disease (AD). However, how the white matter network changes in cognitive impaired patients with subjective cognitive decline (SCD) (a symptom emerging during early stage of AD) and amnestic mild cognitive impairment (aMCI) (a pre-dementia stage of AD) is still unclear. Here, structural networks were constructed respectively based on FA and FN for 36 normal controls, 21 SCD patients, and 33 aMCI patients by diffusion tensor imaging and graph theory. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 60 publications
(51 reference statements)
10
36
0
Order By: Relevance
“…To the best of our knowledge, the only study to date studying network topology in SCD reported preserved white matter organization in SCD. 33 Interestingly, in their study SCD elders also exhibited intermediate network parameter values between HC and MCI. The larger sample size of our study probably allowed us to detect significant differences accounting for the discrepancies in the results.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…To the best of our knowledge, the only study to date studying network topology in SCD reported preserved white matter organization in SCD. 33 Interestingly, in their study SCD elders also exhibited intermediate network parameter values between HC and MCI. The larger sample size of our study probably allowed us to detect significant differences accounting for the discrepancies in the results.…”
Section: Discussionmentioning
confidence: 82%
“…The only study to date addressing this issue employed structural networks to build graph matrices, reporting no differences between healthy elders with and without cognitive concerns. 33 Although from a theoretical perspective graph metrics provide a common framework that allows comparison between networks coming from different types of data, 23 evidence suggests that differences in methodology and relatively small sample sizes may produce divergent results. 16 To the best of our knowledge, this is the first study to date employing graph metrics built from functional data to characterize the evolution of network dynamics throughout the preclinical stages of AD including healthy elders without cognitive concerns (HC), healthy elders with SCD, and MCI patients.…”
Section: Introductionmentioning
confidence: 99%
“…The WM deterministic fiber tracking was terminated when a tracking turn angle was above 45°or the streamline reached a voxel with an fractional anisotropy (FA) < 0.2 between two consecutive voxels (17). We defined the weight of each effective edge between two nodes (i and j) of the WM structure as the product of FN and mean FA along the fiber bundles, and normalized by the average volume of two connecting nodes (w i j = FN * FA/volume) as previous studies described (18,19). Finally, a weighted matrix of 90 × 90 structural network was constructed for each subject.…”
Section: Mr Acquisitionmentioning
confidence: 99%
“…Some DTI studies identified widespread white matter microstructural changes in SCD subjects evidenced by certain DTI parameters modification (Selnes et al, 2012 ). Others concluded that although SCD subjects displayed a trend of intermediate stage between normal ageing and MCI, the structural network during SCD stage was relatively preserved (Wang X. N. et al, 2016 ). Interestingly, still some other study revealed no significant changes of white matter integrity between normal ageing and SCD (Kiuchi et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%